Meis2 controls skeletal formation in the hyoid region - Fabik, Jaroslav; Psutkova, Viktorie; Machon, Ondrej (Frontiers in Cell and Developmental Biology, 2022)
A vertebrate skull is composed of many skeletal elements which display enormous diversity of shapes. Cranial bone formation embodies a multitude of processes, i.e., epithelial-mesenchymal induction, mesenchymal condensation, and endochondral or intramembranous ossification. Molecular pathways determining complex architecture and growth of the cranial skeleton during embryogenesis are poorly understood. Here, we present a model of the hyoid apparatus development in Wnt1-Cre2-induced Meis2 conditional knock-out (cKO) mice. Meis2 cKO embryos develop an aberrant hyoid apparatus – a complete skeletal chain from the base of the neurocranium to lesser horns of the hyoid, resembling extreme human pathologies of the hyoid-larynx region. We examined key stages of hyoid skeletogenesis to obtain a complex image of the hyoid apparatus formation. Lack of Meis2 resulted in ectopic loci of mesenchymal condensations, ectopic cartilage and bone formation, disinhibition of skeletogenesis, and elevated proliferation of cartilage precursors. We presume that all these mechanisms contribute to formation of the aberrant skeletal chain in the hyoid region. Moreover, Meis2 cKO embryos exhibit severely reduced expression of PBX1 and HAND2 in the hyoid region. Altogether, MEIS2 in conjunction with PBX1 and HAND2 affects mesenchymal condensation, specification and proliferation of cartilage precursors to ensure development of the anatomically correct hyoid apparatus.